Nanotechnology in the sports athlete community based on its application in doping detection: a systematic literature review and meta-analysis - Ahmad Chaeroni; Bekir Erhan Orhan; Ardo Okilanda; Kamal Talib; Karuppasamy Govindasamy; Mottakin Ahmed (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study examines the effectiveness and accuracy of nanotechnology applications in doping detection within the athlete community. Nanotechnology offers a novel approach with potential in detecting doping substances more efficiently and accurately. The method used in this study is a Systematic Literature Review (SLR) and meta-analysis, with articles selected from the Scopus and Web of Science (WoS) databases covering the years 2020-2024. The selection process employs the PRISMA method and includes only research articles relevant to the topic. A total of 13 studies were selected for further analysis. The meta-analysis results indicate that the Differential Pulse Voltammetry (DPV) and Enzyme-Linked Immunosorbent Assay (ELISA) methods provide highly accurate and reliable results in doping detection. No significant differences were found between the use of serum and urine as test samples. Additionally, nanocomposite sensors proved to be more effective than regular sensors in detecting doping substances with high accuracy. Key findings from the results include no significant effect distinguishing between the DPV and ELISA methods (Z = 0.53, P = 0.60), no significant heterogeneity among the studies analyzed concerning serum and urine (Chi² = 0.90, df = 2, P = 0.64; Tau² = 0.00), and nanocomposite sensors proving to be more effective than regular sensors (Z = 4.14, P < 0.0001; I² = 0%). In conclusion, nanotechnology has great potential to enhance doping detection in sports. The use of nanomaterials and nanosensors can improve the sensitivity, specificity, and accuracy in detecting doping substances, making it a highly effective tool for maintaining the integrity and health of athletes. This study provides a strong foundation for the development of more efficient and effective nanotechnology-based doping detection technologies in the future.